Swirski mite (suggested common name) Amblyseius swirskii Athias-Henriot (Arachnida: Mesostigmata: Phytoseiidae) - Mahmut Doğramaci; Garima Kakkar; Vivek Kumar; Jianjun Chen; Steven Arthurs (EDIS)
Amblyseius is a beneficial predatory mite endemic to the Eastern Mediterranean region. This species is considered a generalist predator, and readily consumes small soft-bodied pest species as well as pollen or plant exudates. Amblyseius swirskii has attracted substantial interest as a biological control agent of mites, thrips and whiteflies in greenhouse and nursery crops and is currently reared and sold commercially in Europe and North America for this purpose. This 5-page fact sheet was written by Mahmut Dogramaci, Garima Kakkar, Vivek Kumar, Jianjun Chen, and Steven Arthurs, and published by the UF Department of Entomology and Nematology, June 2013.